Longevity of metal-ceramic crowns cemented with self-adhesive resin cement: a prospective clinical study - Lucas Pradebon BRONDANI; Tatiana PEREIRA-CENCI; Vinicius Felipe WANDSHER; Gabriel Kalil PEREIRA; Luis Felipe VALANDRO; César Dalmolin BERGOLI (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract Resin cements are often used for single crown cementation due to their physical properties. Self-adhesive resin cements gained widespread due to their simplified technique compared to regular resin cement. However, there is lacking clinical evidence about the long-term behavior of this material. The aim of this prospective clinical trial was to assess the survival rates of metal-ceramic crowns cemented with self-adhesive resin cement up to six years. One hundred and twenty-nine subjects received 152 metal-ceramic crowns. The cementation procedures were standardized and performed by previously trained operators. The crowns were assessed as to primary outcome (debonding) and FDI criteria. Statistical analysis was performed using Kaplan-Meier statistics and descriptive analysis. Three failures occurred (debonding), resulting in a 97.6% survival rate. FDI criteria assessment resulted in scores 1 and 2 (acceptable clinical evaluation) for all surviving crowns. The use of self-adhesive resin cement is a feasible alternative for metal-ceramic crowns cementation, achieving high and adequate survival rates.